2019
DOI: 10.1021/acs.jafc.8b06362
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation of Thymol in Biodegradable Nanofiber via Coaxial Eletrospinning and Applications in Fruit Preservation

Abstract: The application of the nanofiber film in the field of food preservation was an emerging research direction in recent years. With the functionalization of nanofibers, the quality and safety of food can be better guaranteed. In the present work, thymol as an antibacterial agent was encapsulated into poly­(lactide-co-glycolide) to form core–shell nanofibers by coaxial electrospinning. With such a core–shell nanofiber film, thymol can be slowly released to headspace between food and the nanofiber film, inhibiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
53
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(64 citation statements)
references
References 30 publications
7
53
0
Order By: Relevance
“…Previous studies have introduced drug release control agents in polymer nanoparticles diffusion and biodegradation and reported the rapid release of the drug in the early hours as an "explosion diffusion" [39]. The results of this study in line with previous studies indicate the explosive diffusion of encapsulated Thymol release [40]. Protein stability study showed that temperature as a destructive factor plays an important role in drug preservation [41].…”
Section: Discussionsupporting
confidence: 86%
“…Previous studies have introduced drug release control agents in polymer nanoparticles diffusion and biodegradation and reported the rapid release of the drug in the early hours as an "explosion diffusion" [39]. The results of this study in line with previous studies indicate the explosive diffusion of encapsulated Thymol release [40]. Protein stability study showed that temperature as a destructive factor plays an important role in drug preservation [41].…”
Section: Discussionsupporting
confidence: 86%
“…Zhang et al encapsulated THY in poly(lactide-co-glycolide), PLGA fiber through core-shell coaxial electrospinning [166]. PLGA which is known for its biodegradability and controlled delivery properties [167] has the capability of encapsulating hydrophobic substances and had shown great potential in enhancing the efficiency of delivery in food systems [168,169].…”
Section: Encapsulation Of Yme Essential Oil (Teo) and Ymol (Thymentioning
confidence: 99%
“…Over the past two decades, electrospinning has developed very rapidly, with potential applications of polymer nanofibers having been proposed in a myriad of scientific fields [28,29,30,31]. In addition, the simple single-fluid electrospinning process has advanced to two-fluid coaxial and side-by-side processes, and tri-fluid coaxial and combined coaxial/side-by-side processes.…”
Section: Introductionmentioning
confidence: 99%